2016
DOI: 10.1016/j.phrs.2015.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Activation of a synapse weakening pathway by human Val66 but not Met66 pro-brain-derived neurotrophic factor (proBDNF)

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 50 publications
1
33
0
Order By: Relevance
“…Our data are consistent with a serial synaptic weakening mechanism in which the activation of caspase-3 leads to cleavage of Akt1, removing the tonic inhibition of GSK-3, which subsequently increases pTau and causes inhibition of LTP. Caspase-3, GSK-3 and pTau are all critically involved in LTD, and aberrant LTD expression by these molecules has been implicated in the pathophysiology of synapse weakening and neurodegeneration [18,19,21,[32][33][34][35]. Interestingly, LTP induction can inhibit LTD signalling cascades [17] and, conversely, aberrant activation of LTD and/or synapse weakening signalling cascades inhibits LTP expression [18,19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our data are consistent with a serial synaptic weakening mechanism in which the activation of caspase-3 leads to cleavage of Akt1, removing the tonic inhibition of GSK-3, which subsequently increases pTau and causes inhibition of LTP. Caspase-3, GSK-3 and pTau are all critically involved in LTD, and aberrant LTD expression by these molecules has been implicated in the pathophysiology of synapse weakening and neurodegeneration [18,19,21,[32][33][34][35]. Interestingly, LTP induction can inhibit LTD signalling cascades [17] and, conversely, aberrant activation of LTD and/or synapse weakening signalling cascades inhibits LTP expression [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…A given stimuli (i.e., GCs), therefore, could tip this balance in favor of LTP or LTD by acting as a catalyst for signalling mechanisms associated with one or the other form of plasticity. Previous studies have demonstrated that the inhibition of aberrantly expressed LTD and synapse weakening signalling molecules restores LTP expression ordinarily inhibited in an Aβ neurotoxicity model [19,35].…”
Section: Discussionmentioning
confidence: 99%
“…Instead, proBDNF binds to the pan-neurotrophin receptor p75 Neurotrophin Receptor (p75NTR; Lee et al, 2001 ), to promote cell death (Frade et al, 1996 ; Kuan et al, 1999 , 2003 ), to inhibit neurite outgrowth (Yamashita et al, 1999 ) by modulating RhoA GTPase activity (Yamashita and Tohyama, 2003 ), and to determine presynaptic terminal retraction (Nakayama et al, 2000 ; Yang et al, 2009 ). ProBDNF and p75NTR negatively regulate synaptic transmission and plasticity (Yang et al, 2014 ; Kailainathan et al, 2015 ) and are linked to NMDAR-dependent LTD (Nakayama et al, 2000 ; Rösch et al, 2005 ; Woo et al, 2005 ; Yang et al, 2009 ; Michaelsen et al, 2010 ). A recently generated cleavage-resistant proBDNF knockin mouse (Yang et al, 2014 ) revealed that proBDNF negatively regulates hippocampal dendritic complexity and spine density through p75NTR.…”
Section: Introductionmentioning
confidence: 99%
“…We have recently identified the activation of caspase-3 and glycogen synthase kinase 3 (GSK3β), and phosphorylation of the microtubule associated protein tau (pTau), as being pivotal and necessary end-point signals in synapse weakening (Kimura et al, 2014, Regan et al, 2016. Critically, aberrantly enhanced pTau is a common factor to synapse dysregulation and weakening induced by a variety of factors, including Aβ, stress and neurotrophins (Sotiropoulos et al, 2011, Pooler et al, 2014, Kailainathan et al, 2016. Given the aforementioned importance of CP-AMPAR expression to the initial synaptic alterations induced by stress and Aβ (Whitehead et al, 2013, one favourable hypothesis is that CP-AMPAR expression leads to aberrant synapse weakening via the activation of signaling pathways culminating in tau phosphorylation.…”
Section: Potential Role Of Ca 2+ -Permeable Ampa Receptors In Alzheimmentioning
confidence: 99%